2016
DOI: 10.1016/j.scriptamat.2016.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Hot-pressed chromium doped zinc sulfide infrared transparent ceramics

Abstract: The present study, for the first time, reports the successful consolidation of chromium doped zinc sulfide (ZnS) polycrystalline infrared (IR) transparent ceramics (maximum transmittance of 67% at 11.6 μm) via hot pressing under vacuum. The phase composition of the as-sintered Cr 2+ :ZnS ceramics was determined to be primarily cubic ZnS sphalerite, with a minor amount of hexagonal ZnS wurtzite. Scanning electron microscopy (SEM) observation of the sintered ceramics showed a highly consolidated microstructure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…It is observed that the CLS sample sintered at 1000°C has the best optical performance, with a maximum transmittance of 48.1% at 9.2 μm, which is ascribed to higher densification and lower porosity than the other two samples, as shown in Figure . Based on a comparison of spectra from sample measurement and measurement of the ambient atmosphere, it is determined that the absorption peaks in the 3.2‐4.2 μm range are due to atmospheric absorptions, with the absorption band at 3.2 μm attributed to water, and the peak at 4.2 μm due to CO 2 . The absorption peaks at 6.7 μm and 7.1 μm correspond to the C=O stretching modes in residual carbonates .…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the CLS sample sintered at 1000°C has the best optical performance, with a maximum transmittance of 48.1% at 9.2 μm, which is ascribed to higher densification and lower porosity than the other two samples, as shown in Figure . Based on a comparison of spectra from sample measurement and measurement of the ambient atmosphere, it is determined that the absorption peaks in the 3.2‐4.2 μm range are due to atmospheric absorptions, with the absorption band at 3.2 μm attributed to water, and the peak at 4.2 μm due to CO 2 . The absorption peaks at 6.7 μm and 7.1 μm correspond to the C=O stretching modes in residual carbonates .…”
Section: Resultsmentioning
confidence: 99%
“…Other reports detailed the use of wet chemical methods, which is a favorable technique for producing nanopowders with high sinterability, and these methods allow for atomic‐level mixing and dispersion of dopant ions. Li et al reported the synthesis of spherical and homogenous Cr:ZnS particles with a size of 100‐200 nm through a facile colloidal processing method, with the subsequent transparent ceramics exhibiting a maximum transmittance of 67% at 11.6 μm . Recently, ZnS and Fe:ZnS transparent ceramics were successfully prepared by the consolidation of nanopowders synthesized via co‐precipitation .…”
Section: Introductionmentioning
confidence: 99%
“…Mid‐IR light source is crucial for various applications related to spectroscopy, sensing, and imaging in the molecular fingerprint region . Design and fabrication of new luminescent materials operating in the Mid‐IR region lies in the core of this topic . In order to obtain materials with broadband emission, many approaches such as codoped with rare‐earth ions, embedding Mid‐IR activators into chalcogenide glasses, etc., have been explored .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Design and fabrication of new luminescent materials operating in the Mid-IR region lies in the core of this topic. [9][10][11][12][13] In order to obtain materials with broadband emission, many approaches such as codoped with rare-earth ions, embedding Mid-IR activators into chalcogenide glasses, etc., have been explored. [14][15][16][17][18] Cr 2+ -doped II-VI semiconductors such as ZnS and ZnSe exhibit a unique blend of physical, spectroscopic, and optical parameters, which has been recognized as an excellent Mid-IR luminescent materials.…”
Section: Introductionmentioning
confidence: 99%